THE IMPACT OF INTERPERSONAL COMMUNICATION, A CREATIVE MINDSET, WORK ETHICS, AND JOB SATISFACTION ON THE PERFORMANCE OF JUNIOR HIGH SCHOOL TEACHERS IN LHOKSEUMAWE - Saiful Bahri; Benyamin Situmorang; Darwin Darwin (Asosiasi Dosen Perguruan Tinggi Islam, 2022)
This study seeks to learn about: (1) Innovative work ethic attitudes, (2) Interpersonal interactions about work ethics, (3) A creative approach to job satisfaction (4) Personal interactions that contribute to job satisfaction. 5) The impact of a creative mindset, effective interpersonal communication, a strong work ethic, and job happiness on teachers' effectiveness. Using quantitative methods, a survey approach, a population of 584 teachers, a sample of 237 teachers, a proportional random sampling technique based on the provisions of the model by Slovin, a questionnaire data collection technique called the